Pengaruh literasi keuangan, gaya hidup dan lingkungan sosial terhadap pengelolaan keuangan mahasiswa Studi Kasus Mahasiswa Fakultas Ekonomi Universitas Al-Azhar Medan - Bagus Hadi Pratama; Syamsul Bahri Subakti; Aria Masdiana Pasaribu (BONANZA : Jurnal Ilmiah Ekonomi, Bisnis dan Keuangan, 2026)
This study aims to analyze the influence of financial literacy, lifestyle, and social environment on student financial management at the Faculty of Economics, Al-Azhar University, Medan. The observed phenomenon is the lack of financial management awareness among students despite the growing accessibility of financial information. This research employed a descriptive quantitative approach using a survey method. Primary data were collected through questionnaires distributed to 51 respondents from the 2022 Management Program. The data were analyzed using multiple linear regression with the assistance of SPSS 2024 to test both partial and simultaneous effects among variables. The findings revealed that financial literacy had a positive and significant effect on financial management (tcount = 2.589 > ttable = 1.678; sig. 0.013 < 0.05). Lifestyle had no significant effect (tcount = 1.175 < ttable = 1.678; sig. 0.246 > 0.05), while social environment had a positive and significant influence (tcount = 3.067 > ttable = 1.678; sig. 0.004 < 0.05). Simultaneously, the three variables significantly affected student financial management (Fcount = 26.143 > Ftable = 2.48; sig. 0.000 < 0.05). These results indicate that financial literacy and a supportive social environment are crucial in shaping students’ financial behavior. Conversely, lifestyle does not directly affect financial management due to economic limitations that restrict spending habits. The study concludes that improving financial literacy and fostering a positive social environment can enhance students’ financial management. It is recommended that the university conduct financial education programs and social activities promoting responsible financial behavior.